Pemetaan Perubahan Penggunaan Lahan Pesisir Bali Tenggara dengan Menggunakan Citra Landsat - Wicaksana Karang, I Made Mahendra; Hendrawan, I Gede; Nurweda Putra, I Dewa Nyoman (Journal of Marine Research and Technology; Vol 5 No 2 (2022): AUGUST 2022, 2022)
Bali is an island that has abundant cultural customs; this causes the island Bali to become a favorite tourist destination in Indonesia. Tourism development in Bali is accused of being the cause of the destruction of the agricultural sector due to the large number of agricultural land that has been converted into built-up land. Southeast Bali is one of the areas experiencing land changes in its coastal areas; this can be seen in the reduction in agricultural land in the area. This research uses the remote sensing method to conduct research in the Southeast Bali region. The remote sensing method is effective because it can cover a broad research area, and data can be accessed free of charge by the United States Geological Survey. The images used in this study are Landsat 5 and 8 satellite images. The method used in this study is the maximum likelihood method, which is carried out to identify and classify land use classes. The results show that the building class increases dominant land use from 1995 to 2021, then the most significant land-use change is found in the vegetation area. The results obtained in this study indicate that the accuracy of Landsat 5 and 8 is still quite good. This can be seen from the overall accuracy, which is 92%.